Transformation of Corporate Governance and Property relations in a Digital Society - O. V. Loseva; T. V. Tazikhina; M. A. Fedotova (Управленческие науки)
The need to transform corporate governance and property relations in a digital society stems from the emerging new realities associated with the emergence of digital assets, new intellectual property objects, and the increasing role of human capital and intellectual capital in innovation. The purpose of the work is to identify trends and directions of transformation of property relations and corporate relations that are inherent in the digital society. The methodological basis of the study was the categorical apparatus of economic theory, institutional theory, methods of dialectics, statistical analysis, principles of formal logic, a systematic approach, scientific works of leading domestic and foreign scientists in the field of property theory and corporate relations. The trends that determine the direction of property modification caused by the formation of a digital society are identified; it is proved that the leading forms of ownership are digital assets and intellectual property objects. It is proved that ensuring a technological breakthrough requires strengthening the role of the human factor and a new human-oriented approach to the transformation of corporate relations. Trends of corporate governance modification in the digital society are revealed. The findings can be used in practice by company management when developing corporate governance strategies.